Chimaltenango, Guatemala (Cardinell-Vincent Co.)
On verso: Coffee Production, The wealth of nature in Guatemala, which as all climates and produces delicious fruits of all varieties in abundance, makes the country an agricultural one. There is no coffee superior to hers there may be as good but there is none better. The coffee production for 1914-1915 reached almost one hundred million pounds.